An aromatase inhibitor in combination with Zinc(II) phthalocyanine for targeted therapy of post-menopausal breast cancer. (June 2022) - Yuan, Gankun; Wang, Qilu; Huang, Kunshan; Xue, Jinping; Chen, Juanjuan
Abstract: As a third-generation steroidal aromatase inhibitor, exemestane (EXE ) has been clinically used for postmenopausal advanced breast cancer patients whose condition has progressed after treatment of tamoxifen. However, the further development and application of EXE was limited due to its low solubility and oral bioavailability, inevitable drug resistance and side effects. Based on the unique therapeutic advantages of photodynamic therapy (PDT), a novel aromatase-targeted photosensitizer EX-Pc was synthesized by the combination of EXE and the phthalocyanine photosensitizer. The compound EX-Pc still maintains the superior optical properties of the phthalocyanine photosensitizer upon the introduction of EXE and triethylene glycol chain. Meanwhile, the results of targeted uptake in vitro and in vivo indicated that EX-Pc exhibited high selectivity and affinity for breast cancer cells and tumor tissues, which have the overexpression of aromatase. More importantly, the compound EX-Pc exhibits significant photocytotoxicity and tumor regression ability on breast cancer cells and tumor. In addition, the compound EX-Pc shows negligible side effects and high biological safety. We believe that this is a potential strategy for the treatment of postmenopausal breast cancer. Graphical abstract: Image 1 Highlights: A targeted photosensitizer EX-Pc combined with aromatase inhibitor for the treatment of postmenopausal breast cancer. EX-Pc can preferentially target breast tumor cells with high aromatase expression. EX-Pc exhibits superior cytotoxicity and prominent tumor regression. EX-Pc shows negligible side effects and high biological safety.